LIVING HERITAGE AND SUSTAINABLE INNOVATION: ADAPTIVE BAMBOO ARCHITECTURE IN BALI - Desak Made Sukma Widiyani; Made Ratna Witari; I Ketut Adhimastra; A.A. Ketut Rai Purnama Putra (International Conference on Multidisciplinary Research Perspective, 2025)
This research explores the integration between living heritage and sustainable innovation through the development of adaptive bamboo architecture in Bali, which combines the preservation of traditional cultural values with modern technology to create environmentally friendly architectural solutions. Bamboo architecture has been an integral part of Balinese building traditions that reflects the philosophy of Tri Hita Karana - harmony between humans, nature, and the spiritual world, where bamboo as a material with tensile strength comparable to steel and superior sustainability properties offers solutions with negative carbon footprint. Technological innovations in Balinese bamboo architecture, as seen in projects like Green School and Green Village by IBUKU, have achieved breakthroughs through modern techniques such as the use of adaptive sensors, algorithmic optimization for bamboo element placement, and boron treatment for long-term durability. Adaptive bamboo architecture combines traditional Balinese craftsman expertise with modern engineering techniques, maintaining traditional aesthetic principles such as open spatial layouts and natural ventilation while integrating innovations in connection systems and construction technology. This study demonstrates that the living heritage approach in adaptive bamboo architecture in Bali has the potential to become a global model for sustainable development that respects cultural heritage, bridging the originality of the past with future sustainability through innovative solutions applicable in various global contexts.